Fiji : Background Material. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews Fiji's growth performance since the late 1960s and empirically examines the factors underlying its weak performance. It concludes that Fiji's growth performance, like most of the other Pacific island economies, has been constrained by its remoteness and vulnerability to external shocks. The main constraints to growth associated with small island economies are reviewed along with developments in the policy framework. The paper also analyzes Fiji's growth performance and output behavior from different angles using three approaches: the Hodrick-Prescott filter, a growth accounting framework, and a reduced form equation.